Learn OS X Lion - Mayers, Scott; Lee, Mike.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2011)
You$1 (Bre smart and savvy, but you're also busy. This comprehensive guide to Apple's latest version of OS X, Lion, gives you everything you need to know to live a happy, productive Mac life. Learn OS X Lion will have you up and connected right away. With a minimum of overhead and a maximum of useful information, you$1 (Bll cover a lot of ground in the time it takes other books to get you plugged in. If this isn$1 (Bt your first experience with OS X, skip right to the "What$1 (Bs New in Lion" sections. You may also find yourself using this book as a quick refresher course or a way to learn new Mac skills you$1 (Bve never tried before.s
Keywords: Computer science; Computer Science; Computer Science, general; Computer Applications